2021
DOI: 10.1016/j.nicl.2021.102718
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of spoken language processing in early-stage Parkinson’s disease: An MEG study

Abstract: Highlights Parkinson’s disease (PD) affects motor system and cognitive skills such as language. We used machine learning to study language network connectivity in early-stage PD. Connectivity was probed by classifying MEG responses to different spoken words. PD vs controls were successfully classified using verbs and incorrectly inflected nouns. Early-stage PD exhibits altered language network connectivity despite norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Our data show that beta-band functional connectivity between the LIFC and prefrontal, frontal, and parietal somatomotor regions was negatively associated with speech impairments in patients. Substantial structural and functional connectivity effects have been reported between these regions 97,98 , and functional connectivity between LIFC and superior frontal regions during speech comprehension is reduced in PD 99,100 . Previous studies have also reported increased beta-band connectivity in patients with PD 67 , with indications of clinical significance, although it is still unclear if the relationship is one of impairment 101,102 or compensation 72,[103][104][105] .…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that beta-band functional connectivity between the LIFC and prefrontal, frontal, and parietal somatomotor regions was negatively associated with speech impairments in patients. Substantial structural and functional connectivity effects have been reported between these regions 97,98 , and functional connectivity between LIFC and superior frontal regions during speech comprehension is reduced in PD 99,100 . Previous studies have also reported increased beta-band connectivity in patients with PD 67 , with indications of clinical significance, although it is still unclear if the relationship is one of impairment 101,102 or compensation 72,[103][104][105] .…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that beta-band functional connectivity between the LIFC and prefrontal, frontal, and parietal somatomotor regions was negatively associated with speech impairments in patients. Substantial structural and functional connectivity effects have been reported between these regions 71,72 , and functional connectivity between LIFC and superior frontal regions during speech comprehension is reduced in PD 73,74 . Previous studies have also reported increased beta connectivity in patients with PD 47 , with indications of clinical significance, although it is still unclear if the relationship is one of pathology 75,76 or compensation [77][78][79][80] .…”
Section: Discussionmentioning
confidence: 99%
“…It was previously described that different kinds of neurological disorders, such as brain tumors lead to deviations in the brain’s functional network (Cho et al, 2021; D’Souza et al, 2021; Huang et al, 2014; Hyder et al, 2021; Na et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously described that different kinds of neurological disorders, such as brain tumors lead to deviations in the brain’s functional network (Bartolomei et al, 2006; Cho et al, 2021; De Baene et al, 2017; Derks et al, 2021, 2019; D’Souza et al, 2021; Douw et al, 2013; Huang et al, 2014; Hyder et al, 2021; Na et al, 2018; van Dellen et al, 2012; Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation